Advances in Natural Polymers Composites and Nanocomposites - Thomas, Sabu.; Visakh, P. M.; Mathew, Aji. P.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The book summarizes in a comprehensive manner many of the recent technical research accomplishments in the area of natural polymers. It discusses the various attempts reporting on solving this problem from the point of view of the chemistry and the structure of natural polymers, highlighting the drawbacks and advantages of each method and proposal. Based on considerations of structure - property relations, it is possible to obtain fibers with improved strength by making use of their nanostructures and/or mesophase properties of natural polymers. The book is a unique book with contributions from the experts of the biomaterial area research. it covers all topics related to natural biomaterials such as natural rubber, cellulose, chitin, starch, hemicellulose, lignin, alginates, soy protein, casein and their bionanocomposites and applications. This book is a useful reference for scientists, academicians, research scholars and biotechnologists.
Introduction of natural polymers and their nanocomposites -- Cellulose based blends, composites and nanocomposites -- Chitin and chitosan based blends, composites and nanocomposites -- Starch based blends, composites and nanocomposites -- Recent studies on soy protein based blends, composites and nanocomposites -- Recent studies on casein based blends, composites and nanocomposites -- Recent studies on Alginates based blends, composites and nanocomposites -- Recent studies on lignin based blends, composites and nanocomposites -- Recent studies on hemicelluloses based blends, composites and nanocomposites.
Keywords: Polymers; Materials; Surfaces (Physics).; Materials Science; Characterization and Evaluation of Materials; Continuum Mechanics and Mechanics of Materials; Polymer Sciences